The Material Cultures of the Iranian Home: Cultural Reading - Valibeigi, Mojtaba; Maroofi, Sakineh; Danay, Sara (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
This study aims to identify the main components of the material cultures of Iranian homes. Accordingly, based on the grounded theory, content analyses of plans, diagrams, interviews, and field observations are done. An expert sampling as a type of purposive sampling is used for choosing Iranian traditional houses. The results show core concepts of the material cultures of the Iranian home are confidentiality (Hijab), collaboration, purification, contentment, obedience and submission, and humility. In the form of division of paths (porch), defined communications of spaces, use of different door knockers at the entrance, observance of hierarchy, and access from public to private spaces are defined confidentiality. The second important cultural concept of these homes is the obedience and submission that are induced by religious signs and abstract decorations in the interior space. Humility is also emphasized by avoiding showing off and ostentation and aligning the body and facade of houses with the environment. It seems that the material cultures of the Iranian home have the capability to be the architectural patterns of houses, but when are combined with privacy values and feminine principles.